(untitled) (The Gaze: Journal of Tourism and Hospitality, 2013)
Editors: Bishnu Raj Upreti, Pranil Kumar Upadhayaya and Tikaram Sapkota The Gaze: Journal of Tourism and Hospitality Vol.5 2013 pp.83-90